Cat-scratch disease presenting as multiple hepatic lesions: case report and literature review - Mariana Andrade Baptista; Denise Swei Lo; Noely Hein; Maki Hirose; Cristina Ryoka Miyao Yoshioka; Selma Lopes Betta Ragazzi; Alfredo Elias Gilio; Angela Esposito Ferronato (University of São Paulo, 2014)
Although infectious diseases are the most prevalent cause of fevers of unknown origin (FUO), this diagnosis remains challenging in some pediatric patients. Imaging exams, such as computed tomography (CT) are frequently required during the diagnostic processes. The presence of multiple hypoattenuating scattered images throughout the liver associated with the history of cohabitation with cats should raise the suspicion of the diagnosis of cat-scratch disease (CSD), although the main etiologic agent of liver abscesses in childhood is Staphylococcus aureus. Differential diagnosis by clinical and epidemiological data with Bartonella henselae is often advisable. The authors report the case of a boy aged 2 years and 9 months with 16-day history of daily fever accompanied by intermittent abdominal pain. Physical examination was unremarkable. Abdominal ultrasound performed in the initial work up was unrevealing, but an abdominal CT that was performed afterwards disclosed multiple hypoattenuating hepatic images compatible with the diagnosis of micro abscesses. Initial antibiotic regimen included cefotaxime, metronidazole, and oxacillin. Due to the epidemiology of close contact with kittens, diagnosis of CSD was considered and confirmed by serologic tests. Therefore, the initial antibiotics were replaced by clarithromycin orally for 14 days followed by fever defervescence and clinical improvement. The authors call attention to this uncommon diagnosis in a child presenting with FUO and multiple hepatic images suggestive of micro abscesses.